The extraordinary adventures of ordinary Basil. - Miller, Wiley (New York: Blue Sky Press, 2006)
Bored with his life in a lighthouse, Basil sets out for adventure and soon arrives in a mysterious city in the clouds, where he discovers and tries to foil a plan that threatens the entire world.
Keywords: Adventure and adventurers--Fiction.; Geographical myths--Fiction.; Science fiction